2010
DOI: 10.1002/elps.200900661
|View full text |Cite
|
Sign up to set email alerts
|

Dual CD system in capillary electrophoresis for direct separation of the four stereoisomers of agonist and antagonist melatoninergic ligands

Abstract: In this study, baseline separation of the stereoisomers of six tetrahydronaphthalenic derivatives (agonists and antagonists for the melatonin (N-acetyl-5-methoxytryptamin) binding sites) was successfully achieved using CE and CDs as chiral selectors. The method for the simultaneous chiral separation of the four stereoisomers uses a capillary dynamically coated with polyethylene oxide and a dual CD system. Optimisation was performed first upon the constituents of the CD system, by varying neutral and anionic CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…The results obtained from the present polysaccharides‐based dual systems indicated that both of the neutral and anionic polysaccharide selectors contributed to the enantiorecognition (see Table ), similar to the effective dual CDs systems consisting of a neutral and a charged CD in previous papers . It is well known that polysaccharides have a number of stereogenic centers and functional groups, allowing them to have multiple interactions with enantiomers.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The results obtained from the present polysaccharides‐based dual systems indicated that both of the neutral and anionic polysaccharide selectors contributed to the enantiorecognition (see Table ), similar to the effective dual CDs systems consisting of a neutral and a charged CD in previous papers . It is well known that polysaccharides have a number of stereogenic centers and functional groups, allowing them to have multiple interactions with enantiomers.…”
Section: Resultssupporting
confidence: 83%
“…With two different chiral selectors introduced simultaneously, chiral dual system often leads to a significant enhancement of selectivity and resolution (synergistic effect) due to differences in the complexation mechanisms of the two selectors with the analyte enantiomers . The use of dual CD systems has been reported in some studies, in which different combinations of charged and neutral CDs are employed .…”
Section: Introductionmentioning
confidence: 99%
“…We also report the optimization of experimental conditions for the enantiomeric separation of all the compounds using negatively charged highly sulfated-CDs which have been shown to be particularly effective as single system [17][18][19][20][21][22] or as dual system [23] for the enantiomeric separation of cationic compounds. To the best of our knowledge, no article dealing with chiral separation of such b-carboline derivatives neither in HPLC nor in CE was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, various CSs have been utilized in CE including cyclodextrins (CDs) and their derivatives, chiral crown ethers, chiral surfactants, ligand‐exchange complexes, linear polysaccharides like maltodextrins (MDs), and DNA oligonucleotides, to improve the enantioseparation capability of various classes of analytes . However, to improve the resolution of enantiomers, in some cases, dual systems by a combined use of two chiral reagents/modifiers in the BGE are applied for the chiral separation . Several combinations of the CSs and modifiers were reported until now, including the combinations of a CD and its neutral or ionic derivatives , CD and ionic liquids , CD and glycogen , CD and metal‐amino acid complex and a CD and a chiral surfactant .…”
Section: Introductionmentioning
confidence: 99%